2016
DOI: 10.1111/dote.12511
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of gastro-esophageal reflux disease: a comprehensive review

Abstract: Gastroesophageal reflux disease (GERD) is a common disorder of the upper gastrointestinal tract which is typically characterized by heartburn and acid regurgitation. These symptoms are widespread in the community and range from 2.5% to more than 25%. Economic analyses showed an increase in direct and indirect costs related to the diagnosis, treatment and surveillance of GERD and its complications. The aim of this review is to provide current information regarding the natural history of GERD, taking into accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 80 publications
0
79
0
5
Order By: Relevance
“…The Lyon Consensus regarded LA grade A&B EE as the inconclusive evidence for GERD diagnosis for the reason that LA grade A&B EE can be encountered in 5.0%‐7.5% of asymptomatic controls, and only 1%‐6% of LA grade A&B EE could progress to LA grade C&D EE . A previous study performed among 2580 individuals referred for upper endoscopy in our hospital found that the detection rate of EE was only 4.30%, which was much lower than that of 11.8%‐15.5% in western countries .…”
Section: Discussionmentioning
confidence: 88%
“…The Lyon Consensus regarded LA grade A&B EE as the inconclusive evidence for GERD diagnosis for the reason that LA grade A&B EE can be encountered in 5.0%‐7.5% of asymptomatic controls, and only 1%‐6% of LA grade A&B EE could progress to LA grade C&D EE . A previous study performed among 2580 individuals referred for upper endoscopy in our hospital found that the detection rate of EE was only 4.30%, which was much lower than that of 11.8%‐15.5% in western countries .…”
Section: Discussionmentioning
confidence: 88%
“…Indeed grade B esophagitis might be encountered in asymptomatic controls. Further progression from grade A/B esophagitis to grade C/D and Barrett's esophagus is observed in 1% to 6% and 1% to 12%, respectively, while it may regress to normal endoscopy in 20% to 60% . Thus, grade B esophagitis is not sufficient to unambivalently proof that a subject symptoms are caused by GERD.…”
Section: Gerd Diagnosis: Defining Different Phenotypesmentioning
confidence: 99%
“…7 In that study, the association between GERD and malignancy of the larynx was greater than any other subsite of the upper aerodigestive tract. This has clinical importance as GERD affects up to 30% of the elderly population 35 and is more commonly encountered in elderly or obese patients. 36 GERD is a risk factor for the development of Barrett's esophagus, a premalignant condition of esophageal adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%